Revisiting the extended Svalbard Airport monthly temperature series, and the compiled corresponding daily series 1898–2018 - Nordli, Øyvind; Wyszyński, Przemysław; Gjelten, Herdis M.; Isaksen, Ketil; Łupikasza, Ewa; Niedźwiedź, Tadeusz; Przybylak, Rajmund (Polar research, 2020)
The Svalbard Airport composite series spanning the period from 1898 to the present represents one of very few long-term instrumental temperature series from the High Arctic. A homogenized monthly temperature series is available since 2014. Here we increase the resolution from a monthly to daily basis, and further digitization of historical data has reduced the uncertainty of the series. The most pronounced changes in the 120-year record occur during the last three decades. For the 1991–2018 period the number of days warmer than 0 and 5 °C has increased by 25 (21%) and 22 (59%), respectively, per year compared to the 1961–1990 standard normal. Likewise, comparing the same periods, the number of days colder than −10 and −20 °C has decreased by 42 (32%) and 27 (62%), respectively. During the entire time span of the series, the western Spitsbergen climate has gone through stepwise changes, alternating between cold and warm regimes: 1899–1929 was cold, 1930–1961 warm, 1962–1998 cold and 1999–2018 warm. The latest cold regime was 1.0 °C warmer than the first cold one, and the latest warm regime was 1.7 °C warmer than the previous warm one. For the whole series the linear trend for annual means amounts to 0.32°C/decade, which is about 3.5 times the increase of the global mean temperature for the same period. Since 1991, the rate of warming at Svalbard Airport is 1.7 °C/decade, which is more than twice the Arctic average (0.8 °C/decade, north of 66 °N) and about seven times the global average for the same period.